Neuroradiology Back to the Future: Brain Imaging - Hoeffner, E.G.; Mukherji, S.K.; Srinivasan, A.; Quint, D.J. (American Journal of Neuroradiology, 2012)
SUMMARY: The beginning of neuroradiology can be traced to the early 1900s with the use of skull radiographs. Ventriculography and pneumoencephalography were introduced in 1918 and 1919, respectively, and carotid angiography, in 1927. Technical advances were made in these procedures during the next 40 years that lead to improved diagnosis of intracranial pathology. Yet, they remained invasive procedures that were often uncomfortable and associated with significant morbidity. The introduction of CT in 1971 revolutionized neuroradiology. Ventriculography and pneumoencephalography were rendered obsolete. The imaging revolution continued with the advent of MR imaging in the early 1980s. Noninvasive angiographic techniques have curtailed the use of conventional angiography, and physiologic imaging gives us a window into the function of the brain. In this historical review, we will trace the origin and evolution of the advances that have led to the quicker, less invasive diagnosis and resulted in more rapid therapy and improved outcomes. CPAcerebellopontine angleEDHepidural hematomaLPlumbar punctureNMRnuclear magnetic resonanceSDHsubdural hematoma